The Effect of Realistic Mathematics Education (RME) Approach on Students' Numeracy Literacy Ability - Malim Sutan Lubis; Tanti Jumaisyaroh Siregar (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2023)
The aim of this study was to investigate the effects of learning methodologies based on Realistic Mathematics Education (RME) on the literacy and numeracy abilities of students at SMP Negeri 1 Percut Sei Tuan. The population of this study was the Class VII even semester of SMP Negeri 1 Percut Sei Tuan, which consisted of 8 classes. Class VII-1 served as the experimental class and class VII-2 as the control class when choosing samples from these classes using purposeful selection. There are typically 26 pupils in a class. A quasi-experimental research approach is the Pretest-Posttest Control Group approach. The author developed a three-question essay test to evaluate children's aptitude for solving math problems. In order to examine the effect of RME at a significant threshold of = 0.05, the t-test (independent sample t-test) is used. The hypothesis was tested, and the findings revealed a (2-tailed) sign of 0.000 < 0.05. As a result, it is possible to conclude that the Realistic Mathematics Education approach has a big impact on kids' reading and math abilities.